Link Budget Maximization for a Mobile-Band Subsurface Wireless Sensor in Challenging Water Utility Environments - Chan Hwang See; Abd-Alhameed, Raed A.; Atojoko, Achimugu Alpha; McEwan, Neil J.; Excell, Peter S. (IEEE transactions on industrial electronics (1982), 2018)
A subsurface chamber transceiver system and associated propagation channel link budget considerations for an underground wireless sensor system (UWSS) are presented: the application was a sewerage system for a water utility company. The UWSS operates over the GSM850/900, GSM1800/1900, and Universal Mobile Telecommunications System (UMTS) bands in order to operate with the standard public mobile phone system. A novel antenna was developed to minimize path loss from the underground location: a folded loop type, which is small enough to fit conveniently inside a utility manhole access chamber while giving adequate signal strength to link to mobile base stations from such a challenging environment. The electromagnetic performance was simulated and measured in both free space and in a real manhole chamber. An experimental test bed was created to determine the return loss and received signal strength with different transceiver positions below the manhole chamber access cover. Both numerical and experimental results suggested an optimum position of the unit inside the manhole, combining easy access for maintenance with viable received signal strength. This confirmed that the characteristics were adequate for incorporation in a transceiver designed to communicate with mobile base stations from underground. A field trial confirmed the successful operation of the system under severe conditions.